PROTECTING THE ARCHAEOLOGICAL REMAINS AT THE BORDER AREA: CASE STUDY OF CERAMIC REMAINS AT NATUNA REGENCY - Murdihastomo, Ashar; Seno Bismoko, Dimas (Balai Konservasi Borobudur, 2023)
Natuna is one of the areas in Indonesia that has archaeological remains with the background of past international trade activities through the sea, one of which is ceramics. The number of ceramics remains found on the island can provide information on the early history of civilization on Natuna Island. Ceramics are sought by the residents of Natuna, especially those affected by the northern monsoon, to be traded illegally. Therefore, the question posed in this article is how the archaeological remains protection system is implemented in Natuna Regency. The goal is to minimize illegal activities related to archaeological remains in the Natuna Regency. This article uses primary and secondary data from field research in 2019-2021 and literature studies related to archaeological remains in Natuna. The data was collected through direct observation, excavation, interviews, and a literature review. Then, we did the data reduction. From that, we made an interpretation that is used to solve problems about the protection of archaeological remains. The conclusion obtained is that to minimize illegal activities related to archaeological remains is to collaborate with the activities of three parties, namely the government, stakeholders, and the general public.